Rad51 and BRCA2--New molecular targets for sensitizing glioma cells to alkylating anticancer drugs. - Steve Quiros; Wynand Paul Roos; Bernd Kaina (PLoS ONE, 2011)
First line chemotherapeutics for brain tumors (malignant gliomas) are alkylating agents such as temozolomide and nimustine. Despite growing knowledge of how these agents work, patients suffering from this malignancy still face a dismal prognosis. Alkylating agents target DNA, forming the killing lesion O(6)-alkylguanine, which is converted into DNA double-strand breaks (DSBs) that trigger apoptosis. Here we assessed whether inhibiting repair of DSBs by homologous recombination (HR) or non-homologous end joining (NHEJ) is a reasonable strategy for sensitizing glioma cells to alkylating agents. For down-regulation of HR in glioma cells, we used an interference RNA (iRNA) approach targeting Rad51 and BRCA2, and for NHEJ we employed the DNA-PK inhibitor NU7026. We also assessed whether inhibition of poly(ADP)ribosyltransferase (PARP) by olaparib would enhance the killing effect. The data show that knockdown of Rad51 or BRCA2 greatly sensitizes cells to DSBs and the induction of cell death following temozolomide and nimustine (ACNU). It did not sensitize to ionizing radiation (IR). The expression of O(6)-methylguanine-DNA methyltransferase (MGMT) abolished all these effects, indicating that O(6)-alkylguanine induced by these drugs is the primary lesion responsible for the formation of DSBs and increased sensitivity of glioma cells following knockdown of Rad51 and BRCA2. Inhibition of DNA-PK only slightly sensitized to temozolomide whereas a significant effect was observed with IR. A triple strategy including siRNA and the PARP inhibitor olaparib further improved the killing effect of temozolomide. The data provides evidence that down-regulation of Rad51 or BRCA2 is a reasonable strategy for sensitizing glioma cells to killing by O(6)-alkylating anti-cancer drugs. The data also provide proof of principle that a triple strategy involving down-regulation of HR, PARP inhibition and MGMT depletion may greatly enhance the therapeutic effect of temozolomide.